2017
DOI: 10.22616/foodbalt.2017.032
|View full text |Cite
|
Sign up to set email alerts
|

Sensory properties of high-pressure-treated milk

Abstract: The acceptance and preference of milk and dairy products by consumers is determined by the products sensory characteristics. High pressure processing (HPP) can be applied as an alternative to thermal treatment to provide that sensory quality remains unaffected. The aim of this work was to evaluate the influence of high-pressure treatment on the acceptance of the sensory profile of milk, compared to untreated and thermally-treated milk. Milk was processed at 400 MPa or pasteurized at 78 °C for 15-20 seconds. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Sensory analysis of three different milk samples (untreated, pasteurized, and high-pressuretreated) by untrained and trained panelists utilizing a hedonic scale (1 to 5, with 5 representing the greatest enjoyment)[65]. Original authors did not report the standard deviation of these results.…”
mentioning
confidence: 99%
“…Sensory analysis of three different milk samples (untreated, pasteurized, and high-pressuretreated) by untrained and trained panelists utilizing a hedonic scale (1 to 5, with 5 representing the greatest enjoyment)[65]. Original authors did not report the standard deviation of these results.…”
mentioning
confidence: 99%
“…moisture retention (Pandey et al, 2003) that can be more suitable for soft and fresh cheese production. Our previous study (Liepa et al, (2017) in press) found significant difference (p < 0.05) between milk colour before and after high pressure processing. After high pressure treatment product became more yellowish, this fact can partly prove disintegration of casein micelles during pressurizing.…”
Section: Effect Of Hp Treatment On Curd Firmnessmentioning
confidence: 85%
“…Our previous studies showed the high pressure effect on milk microbiological quality (decrease of colony forming units) (Liepa et al, (2016) in press) and sensory properties (Liepa et al, (2017) in press), but for better understanding how pressure can influence milk properties and for which cheese variety this method of treatment would be the most appropriate, the milk coagulation properties of whole milk were evaluated during this step of research.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations